Optimization of post-weld heat treatment condition of arc-welded T91 steel tubes. (December 2020) - Kumar, Ranjeet; Varma, Anand; Kumar, Y. Ravi; Vashishtha, Himanshu; Jain, Jayant; Neelakantan, Suresh
Abstract: Modified 9Cr–1Mo ferritic/martensitic (T91) steel tubes have been welded with gas tungsten arc welding (GTAW) and shielded metal arc welding (SMAW) processes. The welded tubes have been post-weld heat-treated (PWHT) at selected temperatures (i.e., at 720 °C, 760 °C and 775 °C for different times) below their Ac1 critical temperature (~791 ± 5 °C). The PWHT microstructures, mechanical properties and fracture behavior of welded samples have been investigated. The results suggest that the PWHT temperatures closer to Ac1 critical temperature (i.e., 760 °C and 775 °C) has a strong influence on the properties of the T91 welds. They have shown uniform hardness and enhanced tensile strength and percent elongation as against as-welded and 720 °C – 120 min PWHT condition. Further investigation suggests that the strength and percent elongation for 775 °C – 30 min condition were highest among all the PWHT conditions examined. The observed variation in mechanical properties has been related with the finer microstructural features (mainly grain size and precipitate size). This work further confirms that for PWHT temperatures closer to Ac1, as the holding time increases the failure shifts from base metal (BM) to weld metal (WM) region, predominantly due to de-cohesion at the Mn, Cr, Mo rich coarse precipitate/matrix interface. From this study, a novel PWHT condition at 775 °C – 30 min is being proposed for optimum microstructure and mechanical properties for the T91 steel tube welds. Graphical abstract: Image 1 Highlights: Established post-weld heat treatment (PWHT) effect on microstructures, mechanical properties and fracture in T91 welds. PWHT closer to lower critical temperature (Ac1 ) is more effective in influencing microstructure and mechanical properties. Coarsened M23 C6  type precipitates initiate the failure through de-cohesion at the precipitates-matrix interface. Proposed a novel PWHT at 775 °C for 30 min to achieve optimum microstructural features and mechanical properties.